Understanding the timing of motor imagery: recent findings and future directions - Guillot, A.; Hoyek, N.; Louis, M.; Collet, C. (International Review of Sport and Exercise Psychology, 2012)
Motor imagery (MI) is the cognitive rehearsal of an action without overt motor execution. Among the prerequisites that are important in developing MI training programs, the timing of imagined movements has received a growing body of attention over the last two decades. Nowadays, researchers frequently measure the temporal congruence between actual and MI times, and the difficulty in preserving the temporal features of the actual movement during MI has often been taken as imagery impairment. Interestingly, some data provided evidence that real-time imagery is not the only way to improve performance, while others demonstrated that voluntarily changing the timing of MI can alter the subsequent actual movement speed. The purpose of this review is to provide a complete overview of the variables both being affected and influencing the timing of MI. Differences and similarities between actual and MI times are examined, while the importance of real-time MI and the determination of the factors that may lead athletes to under- or overestimate the actual time during MI are discussed. Finally, practical applications, limits, and future directions regarding measurements of MI times are considered.